Dynamical aspects of a bouncing ball in a nonhomogeneous field - Silveira, Felipe Augusto O.; Alves, Sidiney G.; Leonel, Edson D. [UNESP]; Ladeira, Denis G. (American Physical Society (APS), 2021)
We study some dynamical properties of a charged particle that moves in a nonhomogeneous electric field and collides against an oscillating platform. Depending on the values of parameters, the system presents (i) predominantly regular dynamics or (ii) structures of chaotic behavior in phase space conditioned to the initial conditions. The localization of the fixed points and their stability are carefully discussed. Average properties of the chaotic sea are investigated under a scaling approach. We show that the system belongs to the same universality class as the Fermi-Ulam model.